PERILAKU VERBAL DAN NONVERBAL DALAM RANAH KESEHATAN PADA MASYARAKAT DI DUSUN TAMBRAN KIDUL KECAMATAN SEMIN KABUPATEN GUNUNGKIDUL (KAJIAN ETNOLINGUISTIK) - Die Bhakti Wardoyo Putro; Inyo Yos Fernandez; Wakit Abdullah (PRASASTI: Journal of Linguistics, 2016)
The aims of this study are (1) to describe the view of health and sickness in the cummunity of Tambran Kidul village; (2) to describe verbal and nonverbal behavior in healing and preventing the sickness in the cummunity of Tambran Kidul village; (3) to explain the reasons why verbal and nonverbal behaviors are very essential in healing and preventing the sickness on cummunity of Tambran Kidul village; and (4) to describe mindset, view of life, and worldview in the domain of health on the cummunity of Tambran Kidul village, Semin district, Gunungkidul regency.This study is a descriptive qualitative. Data in this study consisted of primary data and secondary data. Primary data in the form of words in the event said the treatment and prevention of illness-disease using interviews and observation with informants (curer). Secondary data were obtained from books and journals by using literature study method. The data analysis used were ethno science and distributional method with the phases of analysis of domain, taxonomy, componential, and cultural theme. The result of the data analysis is presented through formal and informal method.The result of this study shows that (1) there is a view of health and sickness based on cognition system of Javanese cummunity in Tambran Kidul village; (2) there are verbal and nonverbal behaviors such as (a) text of verbal and nonverbal behaviors are in form of micro and macro structures. Micro structure includes introduction, contents, and cover. Macro structures includes setting and scene, participants, purpose dan goal, act sequences, tone or spirit of act, instrumentalities, norms, and genres. (b) co-text which is kinetic or movement and material element (c) cultural, situational, socio-economic, and spiritual context. (3) the verbal and nonverbal behaviors are very essential because of some reasons (a) verbal behaviors is the realization of faith and hope in God; (b) nonverbal behaviors is the realization of a real action and (c) the existence of inner-energy, (4) the mindset of the Tambran Kidul villagers are; keeping a harmony, peaceful and principle of living together, eling lan waspodho remember and keep watch’, respecting forefathers, and living plainly.. The view of life are: tepa slira ‘mutual respect’; ayom ‘peaceful’, ayem ‘serene’, suka ‘happy’; asih samaning titah ‘love of neighbor’; and nglurug tanpa bala ‘attack without troops’, sugih tanpa bandha ‘rich without possessions’, digdaya tanpa aji ‘divine power without talisman’. The worldview are: the existence of the highest holly spirit, forefathers dhanyang ‘the ancestral spirits who protect the village’, and mbok Sri ‘mother Sri’